Predictors and prevalence of stress, anxiety, depression, and PTSD among university students during the second wave of the COVID-19 pandemic in Turkey - Aslan, Imran; Çınar, Orhan (Frontiers in Psychology, 2023)
It is aimed in the current study to find the prevalence of stress, anxiety, depressions and PTSD, differences according to demographic variables and predictors of mental health problems during second wave of the coronavirus disease (COVID-19) pandemic in Turkey. Differences in exposure to COVID-19 during the first and second waves of the pandemic among students were compared. 754 students from seven universities in different parts of Turkey participated in the survey between November-December 2020 period. Perceived Stress Scale (PSS-10), Generalized Anxiety Disorder (GAD-7), Patient Health Questionnaire (PHQ-9), Checklist-Civilian Version (PCL-C) scale measuring Post-Traumatic Stress Disorder (PTSD) and Satisfaction with Life Scale (SWLS) were used to measure the mental well-being of students. Descriptive statistics, One-way analysis of variance (ANOVA), correlations and multinomial logistic regression methods were used to analyze the data. The prevalence of high stress, high generalized anxiety (GAD-7 ≥ 10), high depression symptoms (PHQ-9≥10) and high PTSD in the total sample were 84.2%, 36.2%, 55.0% and 61.2%, respec-tively. High perceived stress, moderate generalized anxiety disorder, mild depression symptoms, high sever-ity PTSD and moderate satisfaction were found among students in Turkey. Religiosity and spirituality have significant negative correlations with anxiety, depression and PTSD. Religiosity level, gender, relationship status, year of study, physical activity, symptoms of coronavirus, death of a close relative, job loss and eco-nomic status are significant parameters for predicting psychological problems of students in Turkey.